Three reflections in tribute to Monsignor Oscar Arnulfo Romero - González, Luis Armando (Teoría y Praxis, 2022)
Within the framework of Monsignor Romero's canonization, it is important to reaffirm his today, in these times so in need of cultural and moral references of wingspan Three reflections are presented here that, in addition to the claim to reaffirm its validity as a moral and cultural reference for El Salvador, they want be a tribute to that great patriot, pastor, man of faith and servant of the humble that Mons. Óscar Arnulfo Romero was.